2013
DOI: 10.1097/sap.0b013e31823dcec2
|View full text |Cite
|
Sign up to set email alerts
|

Tensor Fascia Lata Flap Versus Tensor Fascia Lata Perforator-Based Island Flap for the Coverage of Extensive Trochanteric Pressure Sores

Abstract: Tensor fascia lata (TFL) musculocutaneous flaps often require a donor site graft when harvesting a large flap. However, a major drawback is that it also sacrifices the muscle. To overcome this disadvantage, we designed a TFL perforator-based island flap that was harvested from a site near the defect and involved transposition within 90 degrees without full isolation of the pedicles. We performed procedures on 17 musculocutaneous flaps and 23 perforator-based island flaps, and compared the outcomes of these sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…However, all these modifications were random-pattern flaps and there were concerns regarding the vascularity of the distal flap. 9 In our case, re-advancement of a skin flap was attempted in the same manner. However, while elevating the flap, it was divided into 2 planes by dissecting the subfascial and submuscular planes.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…However, all these modifications were random-pattern flaps and there were concerns regarding the vascularity of the distal flap. 9 In our case, re-advancement of a skin flap was attempted in the same manner. However, while elevating the flap, it was divided into 2 planes by dissecting the subfascial and submuscular planes.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, unlike a random flap, these flaps were reliable. Moreover, the concept of a “perforator-based flap” is distinct from that of a “perforator flap.” 9 Following to the concept of a “perforator-based flap,” no further dissection is needed to find the proximal source of vessels or to dissect the area around the perforator. 9 Since the undissected proximal portion of the flap always includes numerous invisible “microperforators” that penetrate the TFL, these modifications provide greater versatility and reliability than the perforator flap.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, if the flap is less than 9 cm wide, the donor site can be closed directly without the use of a skin graft. Kim et al 39 reported on their use of the TFL in coverage of large trochanteric pressure sores. A limitation identified in their study was the instability of the T junction where the middle of the TFL flap met the donor site.…”
Section: Discussionmentioning
confidence: 99%
“…Flap surgery is a fundamental reconstruction method for covering defects. Many surgical methods have been proposed, and perforator flaps are commonly used worldwide [1][2][3][4][5]. Perforator flaps are popular because they allow reconstruction of wide defects requiring long pedicles and large rotating arcs while preserving underlying muscles.…”
Section: Introductionmentioning
confidence: 99%